Cryptanalysis of Classical Cryptosystems via Metaheuristics - Nishant kashyap (93613023)
Brute force search is impractical when the search space is large (for instance, consider a binary space that has 2n m-tuples, it is impractical to do brute force if n is greater than or equal to 5). In literature, search heuristics (meta-heuristics) have shown promising results for the cryptanalysis of classical ciphers. In this project, we propose, implement and test new heuristics that are proposed for cryptanalysis of simple substitution cipher and columnar transposition cipher. The proposed heuristics are based on the Genetic Algorithm (GA), Particle Swarm Optimization (PSO) and Cuckoo Search (CS). For verifying efficiency of proposed heuristics, the experiments are conducted. The cryptanalytic results obtained via proposed heuristics are better than the results previously reported in literature. In case of simple substitution cipher, GA has shown better performance than PSO and CS. In case of simple substitution cipher, CS has shown better performance than GA and PSO.
Keywords: INFORMATION SYSTEMS; INFORMATION SECURITY; CRYPTOLOGY